Aplikasi Penjadwalan dan Presensi Sekolah Berbasis Web pada SMK Kemala Bhayangkari 1 Jakarta - Ajeng Lutfiani; Mira Ziveria (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
SMK Kemala Bhayangkari 1 Jakarta is one of the schools where the scheduling process at this school is still done manually by holding meetings first, so that the preparation of subject schedules takes a long time. In the student attendance process and the recapitulation of attendance data is still done manually, namely by recording in the attendance book, so that there is a risk of recording errors, duplicating or manipulating data. This study aims to build a web-based school attendance and scheduling information system at SMK Kemala Bhayangkari 1 Jakarta with a prototyping system development method and using UML (Unified Modeling Language) to describe the activities that users can perform in the system. System development and programming using the PHP programming language and MySQL database. System testing uses black-box-testing. The result of this research is that the system can make it easier for the school to arrange subject schedules and the student attendance process at SMK Kemala Bhayangkari 1 Jakarta.